Understanding brokers, intermediaries, and boundary spanners: a multi-sectoral review of strategies, skills, and outcomes. (28th February 2023) - Neal, Jennifer Watling; Posner, Stephen; Brutzman, Brian
Abstract : Background: Brokers, intermediaries, and boundary spanners (BIBS) bridge research and policy or practice, and can elevate the role of evidence in decision making. However, there is limited integration of the literature across different sectors to understand the strategies that BIBS use, the skills needed to carry out these strategies, and the expected outcomes of these strategies. Aims and objectives: In this review, we characterise the strategies, skills, and outcomes of BIBS across the literature in education, environmental, health and other relevant sectors. Methods: We included 185 conceptual and review papers written in English that included descriptions or conceptualisations of BIBS in the context of knowledge transfer or research use in the education, environmental, health, or other relevant sectors (for example, social services, international development). For each included paper, we extracted and coded information on sector, BIBS strategies, skills, and outcomes. Findings: Our review revealed five strategies used by BIBS that were emphasised in the literature. Specifically, 79.5% of papers mentioned facilitating relationships, 75.7% mentioned disseminating evidence, 56.8% mentioned finding alignment, 48.6% mentioned capacity building, and 37.3% mentioned advising decisions as strategies used by BIBS. Additionally, papers described skills and expected outcomes that were common across these strategies as well as those that were unique to specific strategies. Discussion and conclusions: We discuss implications of these findings for understanding how BIBS interface with knowledge users and producers as well as directions for future research on BIBS and the professionalisation of BIBS roles.